2005
DOI: 10.1523/jneurosci.2269-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anorexigenic Hormones Leptin, Insulin, and α-Melanocyte-Stimulating Hormone Directly Induce Neurotensin (NT) Gene Expression in Novel NT-Expressing Cell Models

Abstract: Neurotensin (NT) is implicated in the regulation of energy homeostasis, in addition to its many described physiological functions. NT is postulated to mediate, in part, the effects of leptin in the hypothalamus. We generated clonal,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 70 publications
1
54
0
2
Order By: Relevance
“…Chromatin immunoprecipitation (ChIP) assays were performed using previously described methodology (Cui et al, 2005). Cells were cross-linked with 1% formaldehyde for 10 min at room temperature and then washed with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were performed using previously described methodology (Cui et al, 2005). Cells were cross-linked with 1% formaldehyde for 10 min at room temperature and then washed with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Immortalized cell lines were generated as described (Belsham et al 2004, Cui et al 2005. Briefly, hypothalami were harvested and dissected from mice at embryonic day 15 (E15), E17, and E18.…”
Section: Cell Immortalization and Subcloningmentioning
confidence: 99%
“…Cell protein was prepared essentially as described previously (Cui et al 2005). Cell protein was collected in 1!…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2C) we evaluated the effects of insulin on four separate cell lines, the mHypoE-36/1, -38, -39 and mHypoE-46 neurons. [18][19][20] Insulin administration to the cell lines led to an increase in the anorexigenic NT; and a decrease in the orexigenic neuropeptides: NPY, AgRP and preproghrelin. Studies within the anorexigenic NT-expressing mHypoE-36/1 and mHypoE-39 neurons demonstrated an approximate 1.5-fold increase in NT mRNA levels following 10 or 100 nM treatment with insulin and α-MSH, but not NPY (Fig.…”
Section: Insulin Signaling and Downstream Effects On Neuropeptide Mrnmentioning
confidence: 97%